Hindu Sampradayas that Integrate Advaita and Dvaita and Catholicism: Creating a Framework for Interreligious Dialogue - Thomas, Tiju (Journal of ecumenical studies, 2021)
In the Second Vatican Council’s Nostra aetate, the Church teaches that, in Hinduism, “men contemplate the divine mystery and express it through an inexhaustible abundance of myths and through searching philosophical inquiry.” In Hinduism, the internal experience of God (anubhava) is of central importance, and it is this that removes ignorance. In the traditions (Sampradayas) of Vishishtadvaita (in Vaishnavism and Shaivism), Dvaitadvaita, and Achintya bheda-abheda (in Vaishnavism), which integrate the Dvaita (dual) and the Advaita (nondual) schools of thought, we see an emphasis in simultaneous difference and nondifference between the human person and the divine, as and when the eternal union occurs. A theological point of contact is noted between the identified Hindu Sampradayas and Catholic teachings on the ultimate relationship between God and the human person. Through the commonalities in the understanding of our eternal destiny and their implications for human life, there are other plausible contacts identified between the theological universes of these Sampradayas and Catholicism. The various Sampradayas chosen here are examined, and their commonalities are identified; then, the points of intersection with Catholicism are studied. Schemas are developed to aid in appreciation of the holy truths that Hindus and Catholics share, and distinctions are drawn out. To communicate the sense and reference in these cases and to promote dialogue, translations render the relevant concepts accessible and relatable to the faithful [End Page 596] of both traditions. For core Catholic concepts, Sanskrit equivalents are constructed and explained, using Indian philosophy to communicate the sense and reference necessary for mutual understanding. The schemas and the framework laid out here should aid dialogue regarding the mystery of God, recognized uniformly in both these Sampradayas and Catholicism.